Antibacterial Activity of Combination Cold Plasma and Parijoto (Medinilla speciosa) Against Staphylococcus aureus and Pseudomonas aeruginosa on Diabetic Ulcer - Anastasia, Fajar Farra; Aziz, Itsna Risqii; Oktaviola, Vanny; Iswara, Arya (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
This study aims to determine the potential of cold plasma (cold plasma) as an antibacterial if combined with Parijoto (Medinilla speciosa) extract against the dominant bacteria in diabetic ulcer infection, namely Gram-positive Staphylococcus aureus and Gram-negative bacteria Pseudomonas aeruginosa with a concentration of 25%, 50 %, 75%, and 100%. This study was an experimental test in vitro using the well diffusion method. The well diffusion method uses an MHA given a 5mm diameter and inserted a 100uL sample then incubates 35 Â± 2 Â° C for 16-18 hours. The results showed antibacterial activity from Cold Plasma with a 10 mm shot distance for 3 minutes with inhibitory zones against S. Aureus 3 mm and against P. aeruginosa 3.35 mm, a combination of Cold Plasma antibacterial activity with parijoto extract with a zone of inhibition of S. aureus 11.7 mm (25%), 14.1 (50%), 16.5 (75%), 17.1 (100%) and against P. aeruginosa 7.7 mm (25%), 9.3 mm (50%), 10.1 mm (75%), 11.7 (100%). the results of the Cold Plasma inhibition zone and Cold Plasma combination with parijoto extract 100% concentration of S. aureus were greater than the inhibition zone for P. aeruginosa. Cold Plasma combination inhibition zones with starch extracts against S. aureus compared to Vancomicin (VA) antibiotics with a 19.9 mm inhibition zone included in the intermediate category, Cold Plasma combination inhibition zone with parijoto juice against P. aeruginosa bacteria compared with Meropenem antibiotics ( MRP) with a 9.7mm inhibition zone included in the sensitive category